Discrepancies in Peak Temperature Times using Prolonged CFD Simulations of Housing Thermal Performance. (June 2017) - Albatayneh, Aiman; Alterman, Dariusz; Page, Adrian; Moghtaderi, Behdad
Abstract: In this paper, CFD analysis was used to determine the internal air temperature over long periods of four full scale housing test modules in Newcastle, Australia exposed to a moderate climate. The influence of different time steps (i.e. 15, 20 30, 35, 40 45, 60, 80, 100, 120, 150, 180 minute intervals) on the discrepancies in peak temperature for the CFD simulations is discussed in the paper. It was found that the average discrepancies in time for internal peak temperatures were between one and five hours compared with the real responses of the testing modules.